Copper-Containing Amine Oxidases and FAD-Dependent Polyamine Oxidases Are Key Players in Plant Tissue Differentiation and Organ Development - Tavladoraki, Paraskevi; Cona, Alessandra; Angelini, Riccardo (Frontiers in Plant Science, 2016)
Plant polyamines are catabolized by two classes of amine oxidases, the copper amine oxidases (CuAOs) and the flavin adenine dinucleotide (FAD)-dependent polyamine oxidases (PAOs). These enzymes differ to each other in substrate specificity, catalytic mechanism and subcellular localization. CuAOs and PAOs contribute to several physiological processes both through the control of polyamine homeostasis and as sources of biologically-active reaction products. CuAOs and PAOs have been found at high level in the cell wall of several species belonging to Fabaceae and Poaceae families, respectively, especially in tissues fated to undertake extensive wall loosening/stiffening events and/or in cells undergoing programmed cell death (PCD). Apoplastic CuAOs and PAOs have been shown to play a key role as a source of H2O2 in light- or developmentally-regulated differentiation events, thus influencing cell wall architecture and maturation as well as PCD. Moreover, growing evidence suggests a key role of intracellular CuAOs and PAOs in several facets of plant development. Here, we discuss recent advances in understanding the contribution of different CuAOs/PAOs, as well as their cross-talk with different intracellular and extracellular metabolic pathways, in tissue differentiation and organ development.